Ocular Manifestations of Von Hippel-Lindau Disease: a Rare Sight- Threatening Condition: Poster Presentation - Case Report - Resident - Elsyanty, Firda Muthia; Widyanatha, Made Indra; Ihsan, Grimaldi; Virgana, Rova; Iskandar, Erwin; Kartasasmita, Arief S. (Ophthalmologica Indonesiana, 2024)
Introduction : Von Hippel-Lindau (VHL) disease is a rare phacomatosis characterized by multi-organ neoplasia which usually manifests in young adulthood. Ocular manifestations of this disease are frequently presented initially before the involvement of other organ systems.Case Illustration : An 18-year-old girl came with a chief complaint of photopsia in the left eye and complete vision loss in the right eye for five years. The visual acuity of the right eye was no light perception and the left eye was 0.8. The anterior segment of the right eye showed iris neovascularization. The posterior segment of the left eye demonstrated multiple elevated red-yellowish lesions fed by a dilated and tortuous vessel. The head CT scan revealed multiple lesions at the pons and cerebellum. The patient was diagnosed with multiple retinal and brain hemangioblastomas due to VHL disease, neovascular glaucoma, and chronic retinal detachment of the right eye due to sequelae of VHL. The patient was treated with cryotherapy and laser photocoagulation of the left eye. Five-month post-cryotherapy follow-up showed the lesions were still active then she underwent the second cryotherapy. The lesions became whitish in appearance with smaller feeder vessels one month after the second cryotherapy and the visual acuity was preserved.Discussion : Retinal hemangioblastoma is the most common ocular manifestation of VHL disease. Prolonged ischemia causes sight-threatening complications including neovascular glaucoma and exudative retinal detachment. Prompt treatment of detected lesions is crucial for visual preservation.Conclusion : Early detection of VHL ocular manifestations plays a critical role in establishing the diagnosis and initiating treatment for a better prognosis.